2014
DOI: 10.1007/s00415-014-7578-2
|View full text |Cite
|
Sign up to set email alerts
|

The utility of polysomnography for the diagnosis of NREM parasomnias: an observational study over 4 years of clinical practice

Abstract: Polysomnography (PSG) is considered the gold standard for diagnosis of non-rapid eye movement (NREM) parasomnias, however its diagnostic yield has been rarely reported. We aimed to assess the diagnostic value of polysomnography in different categories of patients with suspected NREM parasomnia and define variables that can affect the outcome. 124 adults referred for polysomnography for suspected NREM parasomnia were retrospectively identified and divided into clinical categories based on their history. Each po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…No differences were seen between subtypes of NREM parasomnia ( p = 0.271). Fifty‐one (9.9%) of the patients were receiving medications that could affect the diagnostic yield of the vPSG, including 31/512 (6%) on serotonin reuptake inhibitors, two (0.3%) on serotonin–norepinephrine reuptake inhibitors, 13 (2.5%) on tricyclic antidepressants, three (0.5%) on benzodiazepines and two (0.3%) on zaleplon (Fois et al, ). No correlation was found between the administration of the drugs above and the occurrence of NREM‐a, NREM‐A, or RWA and RBD, on the vPSG ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No differences were seen between subtypes of NREM parasomnia ( p = 0.271). Fifty‐one (9.9%) of the patients were receiving medications that could affect the diagnostic yield of the vPSG, including 31/512 (6%) on serotonin reuptake inhibitors, two (0.3%) on serotonin–norepinephrine reuptake inhibitors, 13 (2.5%) on tricyclic antidepressants, three (0.5%) on benzodiazepines and two (0.3%) on zaleplon (Fois et al, ). No correlation was found between the administration of the drugs above and the occurrence of NREM‐a, NREM‐A, or RWA and RBD, on the vPSG ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Sleep‐disrupting pathology, such as OSA and PLMS, has been reported in NREM parasomnia patients and is considered a potential precipitant for parasomnia behaviours, causing arousals and sleep fragmentation (Espa et al, ; Fois et al, ; Guilleminault et al, ; Kothare & Kaleyias, ; Ohayon et al, ). Prior sleep laboratory‐based studies have suggested that sleep studies may identify OSA and/or PLMS in a high proportion of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations